Characterization of SOL plasma flows and potentials in ICRF-heated plasmas in Alcator C-mod. (22nd August 2017) - Hong, R; Wukitch, S J; Lin, Y; Terry, J L; Cziegler, I; Reinke, M L; Tynan, G R
Abstract: Gas-puff imaging techniques are employed to determine the far SOL region radial electric field and the plasma potential in ICRF heated discharges in the Alcator C-Mod tokamak. The two-dimensional velocity fields of the turbulent structures, which are advected by RF-induced E × B flows, are obtained via the time-delay estimation (TDE) techniques. Both the magnitude and radial extension of the radial electric field E r are observed to increase with the toroidal magnetic field strength B φ and the ICRF power. In particular, the RF-induced E r extends from the vicinity of the ICRF antenna to the separatrix when B φ = 7.9 T and P ICRF ≳ 1 MW . In addition, low- Z impurity seeding near the antenna is found to substantially reduce the sheath potential associated with ICRF power. The TDE techniques have also been used to revisit and estimate ICRF-induced potentials in different antenna configurations: (1) conventional toroidally aligned (TA) antenna versus field-aligned (FA) antenna; (2) FA monopole versus FA dipole. It shows that FA and TA antennas produce similar magnitude of plasma potentials, and the FA monopole induced greater potential than the FA dipole phasing. The TDE estimations of RF-induced plasma potentials are consistent with previous results based on the poloidal phase velocity.